Development of Augmented Reality (AR)-based Civics Learning Media to Improve Global Diversity Character in Junior High School - Yunus, Rasid; Adhani, Yuli; Adjie, Zulfikar; Cuga, Candra (Jambura Journal Civic Education, 2024)
This research is motivated by the needs and challenges of secondary school students learning civics in school. So far, Civic learning is still considered a saturated subject area, which has an impact on students' learning motivation and learning outcomes. Through Augmented Reality-based learning media can promote students' global diversity insights, the learning atmosphere is more fun and meaningful. This research is more about the development of augmented reality media designs to promote the understanding of global diversity insights and their impact on students' learning atmosphere. The results showed that the development of AR-based PELAJAR learning media received a percentage of 92.3%, which was included in the "very feasible" category. The benefits of the Augmented Reality learning media are expected to enhance the student's understanding of global diversity and to have an impact on the learning atmosphere in terms of interest and motivation to learn, curiosity and collaboration among the students in Gorontalo. The expected outcome of the research is to provide a reference and prototype for the development of Augmented Reality-based learning media that can be applied to Civics and Social Studies subjects in Junior High School.